MODEL SNOWBALL THROWING: UPAYA PENINGKATAN KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN IPS (STUDI KASUS SD NEGERI 15 KAB. SORONG) - Souisa, Haryo Franky; Tutuarima, Natalya (SOSCIED, 2025)
his study aims to examine and empirically describe the implementation of the Snowball Throwing learning model in improving student learning activeness in Social Studies (IPS) for Grade V students at SD Negeri 15 Sorong Regency. The background of the problem is the low enthusiasm and minimal active involvement of students due to the dominance of conventional, teacher-centered methods, especially in the context of IPS subjects. Student activeness is considered the key to learning success, requiring varied and participatory strategies. Snowball Throwing, a cooperative model that integrates group work with an imaginative question ball game, is an innovative solution to encourage active participation, communication, and collaboration among students. This research uses a descriptive qualitative approach. Data was collected in June 2023 through observation of classroom activities using the Snowball Throwing model, interviews with the principal, IPS teachers, and students, and documentation of relevant archives (RPP, photos, etc.). The implementation was carried out in seven systematic stages, focusing on changing the student's role from passive listening to active discussion and question generation. The results show that the implementation of the Snowball Throwing model was successful in significantly increasing student learning activeness. This success is evidenced by the fulfillment of eight indicators of student activeness, including participation in assignments, problem-solving, active questioning, and group discussion. Although there were challenges, such as the drastically reduced class time (from 3x45 minutes to 40 minutes ) and disturbances from peers , the activeness increased substantially from the first to the second meeting. Students reported that the model was fun, reduced boredom, and made the IPS material easier to understand, fostering greater responsibility and confidence in expressing opinions. This confirms that the model effectively stimulates concrete activeness and participation in the classroom. Keywords : Snowball Throwing, Learning Activeness, Social Studies